2021
DOI: 10.3389/fpubh.2021.777426
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Did Not Change the Personal Protective Behaviors of Healthcare Workers in China

Abstract: Personal protective behaviors of healthcare workers (HCWs) and dynamic changes in them are known to play a major role in the hospital transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this study, 1,499 HCWs in Chinese hospitals completed an online survey about their knowledge on SARS-CoV-2 transmission and their personal protective behaviors before and after coronavirus disease 2019 (COVID-19) vaccination. Of all the respondents, 89% were vaccinated at the time of the survey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In Part 3, risk assessment, although almost all nurses are vaccinated, they are still afraid of being infected while working with a positive patient. These findings are supported by the study by Zhang et al ( 53 ); they revealed that nurses did not change their protective behavior even after getting vaccinated. While COVID-19 vaccines are effective for immunizing people, they do not guarantee 100% complete protection ( 12 ).…”
Section: Discussionsupporting
confidence: 81%
“…In Part 3, risk assessment, although almost all nurses are vaccinated, they are still afraid of being infected while working with a positive patient. These findings are supported by the study by Zhang et al ( 53 ); they revealed that nurses did not change their protective behavior even after getting vaccinated. While COVID-19 vaccines are effective for immunizing people, they do not guarantee 100% complete protection ( 12 ).…”
Section: Discussionsupporting
confidence: 81%
“…Vaccinated people and those who had received the COVID-19 vaccine booster dose, should continue to take all appropriate recommended precautions to protect themselves and others from the disease. To the best of our knowledge, the literature has neglected to investigate the change in plans to use preventive measures among those who had received a COVID-19 booster dose, and only a few studies have analyzed the compliance with the recommended prevention behaviors among vaccinated individuals [ 6 , 7 , 8 , 9 ]. Therefore, in this current epidemiological scenario, the present research offers an important contribution to the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that close contacts, which include short-range airborne, are a high risk transmission route ( [4] , [5] ). Restaurants may have an extremely high rate of SARS-CoV-2 exposure via the close contact route because of high close contact rate (20%) without masks ( 1 ).…”
Section: Dear Editormentioning
confidence: 99%